A reassessment of the higher-order factor structure of the German Schizotypal Personality Questionnaire (SPQ-G) in German-speaking adults. (November 2018) - Barron, David; Voracek, Martin; Tran, Ulrich S.; Ong, Hui San; Morgan, Kevin D.; Towell, Tony; Swami, Viren
Highlight: Confirmatory factor analysis indicated support for the 4-factor structure of SPQ-G. Other models (2- and 3-factor models) had poorer fit indices. Partial measurement invariance was obtained across migrational group and sex. Non-migrants had higher Cognitive-Perceptual scores than German migrants. Abstract: The Schizotypal Personality Questionnaire (SPQ) is a widely-used self-report instrument for the assessment of schizotypal personality traits. However, the factor structure of scores on English and non-English translations of the SPQ has been a matter of debate. With little previous factorial evaluation of the German version of the SPQ (SPQ-G), we re-assessed the higher-order factor structure of the measure. A total of 2, 428 German-speaking adults from Central Europe (CE) and the United Kingdom (UK) completed the SPQ-G. Confirmatory factor analysis – testing proposed 2-, 3-, and 4-factor models of SPQ-G scores – indicated that the 4-factor solution had best fit. Partial measurement invariance across cultural group (CE and UK) and sex was obtained for the 4-factor model. Further analyses showed CE participants had significantly higher scores than UK participants on one schizotypal facet. These results suggest that scores on the SPQ-G are best explained in terms of a higher-order, 4-factor solution in German migrant and non-migrant adults.